Ancestral halls and ‘modern temples’: museums in postcolonial Hong Kong - Yu, SYJG (2022)
In this thesis, I examine how the meanings and roles of museums, as a worldwide cultural phenomenon that has been initiated in Europe, are adapted and transformed according to local contexts beyond Europe. My ethnographic research explores the specific context of post-colonial Hong Kong and examines the rise of non-government museums. I argue that this phenomenon is the result of nostalgia, rising historical and cultural consciousness, increasing ‘museum-mindedness’ and the continuing identity dilemma experienced by residents, both young and old, of postcolonial Hong Kong. I have critically analysed five types of museum-like institutions in Hong Kong, namely: ancestral halls, governmental, independent, amateur, and school history museums. Investigating recent developments of museums in Hong Kong through the lens of Chinese ancestral halls, I argue that ancestral halls are, in effect, ‘precursory museums’ for those that have been created more recently. Enabled by objects, spatial experience and social interactions, Chinese ancestral halls and contemporary Hong Kong museums both aim to preserve and transmit cultural knowledge and, in the process, facilitate identity construction. Set up by all kinds of actors, ranging from independent trusts to individual amateurs, non-government museums in Hong Kong are diverse in their forms but united by the same aim and function: to preserve and interpret local heritage in their own ways and according to indigenous criteria.